Concreto auto-adensável utilizando resíduos de caulim - Diniz, Marcelo Andrade (2010)
Self-compacting concrete (SCC), considered one of the greatest advances in concrete technology, is characterized by its special capacity of filling ability, passing ability and resistance to segregation by the action of its own weight without the presence of other external forces. Taking into consideration the numerous cities and their industries that have caused a considerable increase in the production of solid waste, including industrial waste in SCC has brought about significant environmental benefits. This study aimed to develop a SCC with inclusion of waste from the manufacturing of kaolin, specifically from what is called birra and borra . The most common producers of SCC used limestone filler. In the production of SCC the mix-design method Tutikian (2007) and Gomes (2002) were used as a base, the Marsh funnel and miniature slump tests for paste composition and the compactability test of materials for the fabrication of granulometric skeletons. In order to evaluate the properties of SCC in fresh state tests, the slump flow test, slump flow test T50cm, V-funnel, V-funnel 5min, L-box, U-box and J-ring were used. The possibility of using waste from the kaolin beneficiation in a SCC was proven, where the borra was used as fine material and birra as a replacement for aggregates. In the hardened state, testing of compressive strength were carried out on the 7th and 28th days, resulting in resistance rate of approximately 20 to 40MPa.